Prevalence and associated factors of apathy in Chinese ALS patients - Wei, Qian-Qian; Guo, Yuan; Li, Shirong; Yang, Tianmi; Hou, Yanbing; Ou, Ruwei; Lin, Junyu; Jiang, Qirui; Shang, Huifang (Frontiers in Psychology, 2023)
Objective: This study aimed to explore the prevalence and clinical correlates of apathy in amyotrophic lateral sclerosis (ALS) in a cohort of Chinese patients. Methods: A total of 1013 ALS patients were enrolled in this study. Apathy was recorded during face-to-face interviews using Frontal Behavioural Inventory, and other patient characteristics, including depression, anxiety, and cognitive function, were collected using Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), and Chinese version of Addenbrooke’s Cognitive Examination-revised. Health-related quality of life of ALS patients and their caregivers was also evaluated, and the potential factors associated with apathy were explored using forward binary regression analysis. Survival was analysed using the Cox proportional hazards model. Results: The prevalence of apathy in all patients was 28.9%. Patients in the late disease stage had a higher prevalence of apathy than those in the early disease stage. Furthermore, patients with apathy had a lower ALS Functional Rating Scale revised (ALSFRS-R) score, higher HDRS score, HARS score and higher proportion of reported problems in the anxiety/depression. Additionally, their caregivers had higher score of depression and higher Zarit-Burden Interview scores. Multivariate regression analysis revealed that apathy in ALS was associated with the onset region (P=0.027), ALSFRS-R score (P=0.007), depression (P=0.001) and anxiety (P<0.001). Apathy had a significant negative effect on survival in ALS patients (P=0.032). Conclusions: Apathy is relatively common (28.9%) in Chinese patients with ALS. Apathy is related to both the severity of the disease, and the presentation of non-motor symptoms in ALS, such as depression and anxiety disorders. Apathy is an independent prognostic factor for survival and requires early intervention and management.